Snow white and the seven dwarfs: the story of Snow White (Disney Press Los Angeles, California, 2016)
"Escape into Snow White's spectacular story. With an evil queen and her magic mirror, seven whimsical dwarfs and their sparkling mine, this deluxe storybook retelling of the classic animated film is a treasure to behold."--Back cover